HIV prevention under the view of indigenous women from the Potiguara tribe* - Rafaela Gerbasi Nóbrega; Natalia Aparecida de Oliveira; Édija Anália Rodrigues de Lima; Ana Cristina de Oliveira e Silva; Sandra Aparecida de Almeida; Jordana de Almeida Nogueira (Universidade Federal de Santa Maria, 2020)
Objective: to analyze the way in which the prevention of infection by the human immunodeficiency virus (HIV) is configured under the view of women from the Potiguara ethnic group. Method: a qualitative study involving 256 women from three indigenous villages in Paraíba-Brazil The information was collected in 2015, through the Free Word Association Test and semi-structured interviews. The corpus was analyzed from the Descending Hierarchical Classification, Content Analysis, and Similitude Analysis. Results: three classes of content related to HIV prevention were identified: "Vulnerability to HIV infection"; "Protective measures"; and "Need for health education". The word "condom" occupied the central position in the similarity analysis. Conclusion: although they recognize the means for preventing HIV, it is difficult to perform protected sexual practices. Such condition is crossed by social and gender inequalities, which extend to the reality of non-indigenous women.